Sterilization, Multiplication and In Vitro Conservation of Germplasm Taro (Colocasia esculenta [L.] Schott) in BB BIOGEN - Muhamad Sabda; Dedy Darnaedi; Dodin Koswanudin (JURNAL SAINS NATURAL, 2022)
The taro plant (Colocasia esculenta) has the potential as an alternative food that can be processed into various processed food products. Efforts to save germplasm ex-situ through taro conservation in vitro can be a backup for existing collections in the field. The activity was carried out at the in vitro conservation laboratory of the genetic resource management research group, the Bogor Institute for Research and Development of Biotechnology and Agricultural Genetic Resources (BB Biogen). A total of 15 accessions were used as explant material for sterilization, explants were grown on MS media, and then at 10 DAP, the percentage of live, contaminated, and dead explants was observed. The average sterile explants in all accessions were 34.01%, contaminated explants were 65.08%, and dead explants were 0.91%. Multiplication was carried out by subculture of the two most plantlets into the propagation medium, namely: (1) control MS, (2) MS + Thidiazuron 0.25 ppm, (3) MS + Thidiazuron 0.5 ppm, (4) MS + Thidiazuron 2 ppm, (5) MS + BA 0.5 ppm, (6) MS + BA 1 ppm, and (7) MS + BA 3 ppm. On conservation media until 5 months, the best response was shown in M3 (paclo 2 ppm) and M4 (mannitol 4%).Keywords: Aksesion; Explan; Media; ShootsABSTRAKSterilisasi, Multiplikasi, dan Konservasi In Vitro Plasma Nutfah Tanaman Talas (Colocasia esculenta) di BB BIOGENTanaman talas (Colocasia esculenta) memiliki potensi sebagai pangan alternatif yang dapat diolah menjadi berbagai produk olahan pangan. Upaya penyelamatan plasma nutfah secara ex situ melalui konservasi talas melalui in vitro dapat menjadi cadangan (back up) koleksi yang ada di lapang. Kegiatan dilaksanakan di Laboratorium konservasi in vitro kelompok peneliti Pengelolaan Sumber Daya Genetik, Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian (BB Biogen) Bogor. Sebanyak 15 aksesi digunakan sebagai materi eksplan untuk di sterilisasi, eksplan ditanam pada media MS, dan kemudian pada 10 HST diamati persentase eksplan yang hidup, terkontaminasi, dan mati. Rata–rata eksplan steril pada seluruh aksesi sebanyak 34,01%, eksplan terkontaminasi 65,08%, sedangkan eskplan yang mati sebanyak 0,91%. Multiplikasi dilakukan dengan subkultur terhadap dua planlet terbanyak ke dalam media perbanyakan, yaitu : (1) MS kontrol, (2) MS + Thidiazuron 0,25 ppm, (3) MS + Thidiazuron 0,5 ppm, (4) MS + Thidiazuron 2 ppm, (5) MS + BA 0,5 ppm, (6) MS + BA 1 ppm, dan (7) MS + BA 3 ppm. Pada media konservasi until the age of 5 months, the best response was shown in M3 (paclo 2 ppm) and M4 (mannitol 4%).Kata kunci: Aksesi; Eksplan; Media; Tunas